Clinical and radiological characteristics of patients with spontaneous and post-traumatic subarachnoid hemorrhage: a retrospective observational study - Šabotić, Irfan; Ilić, Jovan; Kostić, Aleksandar; Djordjević, Marija; Nikolov, Vesna; Radisavljević, Miša; Jelenković, Boban; Stojanović, Nikola (Vojnosanitetski pregled, 2023)
Background/Aim. Several serious complications can accompany both spontaneous and post-traumatic subarachnoid hemorrhage (SAH) such as the development of intracranial hypertension, hydrocephalus, re-bleeding, cerebral hypoxia, cerebral vasospasm, impaired pituitary function, electrolyte imbalance, and electrocardiographic (ECG) abnormalities. Although there is a declining trend in mortality, the treatment of SAH and its complications represents a challenge even in imposing neurosurgical centers. The aim of the study was to compare some clinical characteristics and complications between spontaneous and post-traumatic SAH. Methods. The retrospective study included 138 patients treated at the Department of Neurosurgery from January 2018 to January 2023. There were 71 patients with spontaneous and 67 patients with post-traumatic SAH. Results. A predominance of spontaneous SAH in female and post-traumatic SAH in male patients (p < 0.001) was found. There was a statistically significant difference in the frequency of hydrocephalus between groups of spontaneous and post-traumatic SAH patients (p = 0.013). Cerebral vasospasm was significantly more prevalent in patients with spontaneous SAH (p < 0.001). A statistically significant association was also obtained between the thickness of the coagulum in these two groups (p < 0.001). Patients with spontaneous SAH were significantly more likely to have a negative T wave in ECG findings (p < 0.001). Furthermore, there was no statistically significant difference regarding electrolyte imbalance in these two groups of patients with SAH. Conclusion. There were statistically significant differences between gender distribution, the frequency of abnormal ECG findings in the form of a negative T wave, greater coagulum thickness, vasospasm occurrence, and a higher rate of hydrocephalus in patients with spontaneous SAH compared to patients with post-traumatic SAH.